KURANGNYA MANAJEMEN PERAWATAN DIRI DAN PENGENDALIAN TEKANAN DARAH PASIEN HIPERTENSI DI DAERAH LAHAN BASAH - Guna, Stephanie Dwi; Agrina, Agrina; Herlina, Herlina; Nopriadi, Nopriadi; Nurhayati , Nurhayati (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2024)
Hypertension is the non-communicable disease with relatively high prevalence in Indonesia. The continuity of hypertension care is crucial for patients to control their blood pressure and prevent complications of this silent-killer disease. This research aims to analyze the self-management and blood pressure control of hypertension patients in wetland areas. Taking place in the area supported by the Faculty of Nursing, Universitas Riau, which is the coastal area of the Siak River, Pekanbaru, this research was a quantitative study; descriptive analytic. Thirty participants who were hypertensive patient without complication were chosen by purposive sampling. The instruments were a hypertension patient self-management questionnaire and a digital sphygmomanometer to measure blood pressure. The result showed the majority of the participants was in productive age; adult (33%) and pre-elderly (47%). The result also showed that no participant had good self-management, and most of them had poor self-management (53%). It also revealed only 23% of participants consume anti-hypertension medications regularly, while the rest of them is not taking medication at all. Most of the participants’ blood pressures were uncontrolled (97%). The average systolic pressure was 159 mmHg with maximum point at 238 mmHg and diastolic pressure was 98 mmHg with maximum point at 141 mmHg. This research indicates the urgency in dealing with hypertension, especially in research locations.